Perbedaan Hasil Belajar Matematika Antara Siswa Yang Menggunakan Pedekatan Komputasional Dengan Pendekatan Pemecahan Masalah Polya - Chusniah, Risa; Supriyo; Ani Afifah (STAI Al-Bahjah, 2025)
The purpose of this study is to find out how the mathematics learning outcomes of students in grade VIII of SMP Negeri 4 Pasuruan are different from students taught by the Polya problem-solving method. This study was conducted using a quasi-experimental plan with the Non-Equivalent Control Group model. There were 28 students in class a who received treatment through the computational thinking approach and 23 students in class B who received treatment through the Polya approach. The initial test, or pretest, and the final test, or posttest, on the data centering material are research tools. Because the data was not normally distributed, the data analysis was carried out using the Wilcoxon Signed Ranks test to establish a difference between the pretest and posttest scores in each group. In addition, the Mann-Whitney U test is used to compare posttest scores between groups. The results of the Mann-Whitney U test showed that there was a significant difference between the two groups. Based on indicators of learning outcomes, accuracy, systematics, numeracy skills, problem identification, and reflection, students taught with a computational thinking approach showed an improvement compared to the Polya group. Research shows that the thinking approach is more effective in encouraging systematic, analytical, and strategic ways of thinking. The results show that computational thinking is effective in mathematics learning to improve students' problem-solving abilities.